Experimental Study of the Airside Performance for Interrupted Fin-and-tube Heat Exchanger with Hydrophilic Coating under Dehumidifying Conditions - 马小魁 丁国良 张圆明 (Shanghai jiao tong da xue xue bao, 2009)
The airside heat transfer and friction characteristics of seven interrupted fin-and-tube heat exchangers with hydrophilic coating under dehumidifying conditions are experimented. The effects of number of tube rows, fin pitch and inlet relative humidity on airside performance are analyzed. The test results show that the influence of fin pitch on the friction characteristic under dehumidifying conditions is similar to that under dry surface, and the friction factors decrease slightly with the increase of number of tube rows. The heat transfer performance decreases as fin pitch and number of tube rows increases. The heat transfer performance and the friction characteristic are independent of inlet relative humidity. Based on the test results, heat transfer and friction correlations in terms of the Colburn j factor and Fanning f factor, are proposed to describe the airside performance of the interrupted fin geometry with hydrophilic coating under dehumidifying conditions. The correlation of the Colburn j factor gives a mean deviation of 9.7%, while the correlation of the Fanning f factor shows a mean deviation of 7.3%.